Computerized Behavioral Interventions: Current Products and Recommendations for Substance Use Disorder Treatment. Issue 4 (2nd October 2017) - Patterson Silver Wolf (Adelv Unegv Waya), David A.; Hughes, Maggie; Maher, Nakomis; Shen, Yangqian; Shore-Fitzgerald, Christine; Wang, Yang
Abstract : Unlike traditional methods of delivering substance use disorder (SUD) and mental health treatment, computerized behavioral interventions deliver services via computers, smartphones, and other electronic devices. In recent years, there has been a proliferation of Web-based treatment programs designed for certain target populations. Studies have shown that many of these programs are evidence-based, and some are just as effective as traditional in-person interventions. This article reviews current computerized behavioral interventions and makes recommendations for how these tools can be incorporated into SUD treatment services.